Room-Temperature Stille Coupling of Tetraarylstannanes via Palladium-Catalyzed C–H Activation - Xue, Dong; Li, Jing; Liu, Yu-Xia; Han, Wen-Yong; Zhang, Zun-Ting; Wang, Chao; Xiao, Jianliang (Synlett, 2012)
An effective room-temperature Stille cross-coupling of aryl ureas with tetraarylstannanes via palladium-catalyzed C–H bond activation is reported, providing a mild method for direct arylation of aromatic C–H bonds.
Keywords: palladium; room temperature; Stille coupling; tetraarylstannanes; C–H activation